Investigating the effects of corporate governance on the relationship between earning management and corporate performance in the Bursa Malaysia - Nasiri, Mojtaba; Sofian, Dr.Saudah (International Journal of Engineering and Technology, 2018)
The lack of transparency in financial reports has several reasons, but the most important is earnings management practice which is implemented by managers. Indeed, managers by using Earnings Management tools manipulate accounting information to achieve some goals. Corporate governance, whose primary goal is to deal with identifying potential mechanisms in which the shareholders of a corporation have more power and exercise control over the managers to protect their interests. This study investigates whether corporate governance affects the relationship between earnings management and firm performance by using listed companies’ data in Bursa Malaysia. Data from FTSE Russell has been used by applying the intersection function to the constituents of FTSE Top 100 Bursa Malaysia during the years 2011 to 2015, which includes 59 companies in the form of 295 company-year. The results show that discretionary accruals (DAs) have a significantly negative effect on return on equity and has significant positive effects on Tobin’s q in the case of lack of consideration corporate governance moderating effect. On the other hands by considering the moderating effect of corporate governance variables, this equation has been changed, and the negative effect of earning management effects turns to neutral on ROE, and This effect has not been changed regarding Tobin’s q.